Persepsi Penggemar Pasangan Boys Love (BL Ship) terhadap Homoseksualitas - Sintya Frank Sianturi; Ahmad Junaidi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
These past few years, Thailand’s entertainment industry has been increasing their production of Boys’ Love series and movies. The genre blew up in 2014, and until 2020, around 57 BL series had been produced and released. This has led to the phenomenon of the escalation of the number of Thai BL fans in Indonesia. The aim of this research was to find out how BL Ship’s fans or shippers perceive homosexuality. Perception is a meaning making activity of a sensory stimulus through gathering and interpreting process of information or message. To elaborate it, this research used the qualitative research method with case studies approach towards the members of BL ship Off Jumpol-Gun Atthaphan’s fans kingdom. Data was gathered by interview, observation, and documentation. To analyze it, researcher conducted Glaser and Strauss’s constant comparative method, and Mahpur’s coding steps. The results showed that shippers’ perception of homosexuality more or less got affected by what they consumed through media, such as BL series and ships. Along the way, their cultural background, religious views, personal experiences and values also influenced their views of the meaning of homosexuality. Researcher suggest that the professionals who are working in the industry of this genre to be mindful and take extra care since it’s going to affect the audience’s perception.Beberapa tahun terakhir, industri hiburan Thailand semakin gencar memproduksi drama serial dan film romantis bergenre Boys’ Love (BL). Sejak pertama kali meledak tahun 2014 hingga 2020, terdapat setidaknya 57 serial drama BL yang telah dibuat dan ditayangkan. Hal ini menyebabkan fenomena peningkatan penggemar pasangan Thai Boys’ Love (BL Ship) di Indonesia. Penelitian ini bertujuan untuk melihat bagaimana persepsi penggemar BL Ship terhadap homoseksualitas. Persepsi merupakan kegiatan pemberian makna pada stimulus sensorik yang diperoleh melalui proses menyimpulkan dan menafsirkan informasi dan atau pesan. Metode yang digunakan adalah metode penelitian kualitatif dengan pendekatan studi kasus. Subjek dalam penelitian ini adalah anggota kelompok penggemar pasangan BL Off Jumpol-Gun Atthaphan. Teknik pengumpulan data yang digunakan adalah teknik wawancara, observasi, dan dokumentasi. Data yang telah terkumpul kemudian direduksi, dikategorisasi, disintesisasi, dan kemudian ditarik kesimpulannya. Hasil penelitian menunjukkan bahwa terdapat faktor personal dan situasional yang mempengaruhi persepsi individu terhadap homoseksualitas. Latar belakang budaya, kepercayaan secara religius, dan nilai-nilai dari sekitar maupun pribadi individu turut mengambil peran dalam proses pembentukan persepsi individu atas homoseksualitas. Penting bagi pegiat genre ini untuk memerhatikan apa yang diproduksi karena apa yang ditampilkan akan mempengaruhi persepsi yang diterpanya.